A model for a binary multi level marketing compensation plan - Co, Prince Dingwell K. (Animo Repository, 2000)
Abstract. At present, going rate pricing method is used to establish a binary Multi Level Marketing (MLM) compensation plan. The going rate pricing method fails to consider cost, demand factors and the distributor network growth behavior in the binary system. Knowing this, the proponents aim to incorporate planning, forecasting and distributor behavior to come up with an optimal compensation plan. This is done by using Binary structure simulation that takes into account the actual Multi Level Marketing company profit, free profit, distributor price, retail price, total overhead cost, target profit, percent distributor cut off, minimum group business volume, percent retail profit of the distributor and the Binary network structure. A mathematical model in the form of Multi Integer Non Linear Program (MINLP) was developed based from interviews with credible MLM professionals, related literatures and real binary MLM policies. The mathematical model is integrated with a binary simulation to determine the optimal compensation plan that takes the MLM company's point of view. The developed MINLP was validated using the Microsoft Excel solver function. And the study prides itself with a software called PriWiRi that packs the whole mathematical model into one user friendly program that was written in Microsoft Visual Basic and runs in Microsoft Excel. Validation of the MINLP model using a set of industry data results to an optimized objective function. The objective function obtained a 71,045 pesos profit for the MILM company as against the going rate pricing methods profit of 22,454 pesos. Having a superior profitability compared to the going rate pricing method confirms and authenticates the importance and significance of the proposed model. Likewise, the study proves to meet and even exceed the target profit of a MLM company. Furthermore, the study gives out compensation to more distributors as against the present method of going rate pricing and even prevents the compensation plan to give out unwarranted or extreme group rebates.